Well Dear Lakeisha ;
( 27x / 9 ) ( x^8 / 3x^5 )
Step 1
27x / 9
{ 27/ 9 = 3 }
3 * x = 3x
Step 2
( x^8 / 3x^5)
rewrite this like that
1/3 ( x ^ 8 / x ^ 5 )
{ as you know if " x ^ a / x ^ b = x ^ ( a - b) " }
1/3 ( x ^ (8 - 5)) = 1/3 * ( x^3 ) = ( x^3 / 3 )
Step 3
(3x) ( x^3 / 3 ) { simplify ' 3 ' }
so we have ;
x * ( x ^ 3 )
{ as you know if " (x^a) * (x^ b) = x^ (a+b) " }
x * ( x ^ 3 ) = x^ ( 1+3) = x^4
The Total Result is ;
( 27x / 9 ) * ( x^8 / 3x^5 ) = x ^ 4
Good Luck Dear.
2006-10-11 07:54:54
·
answer #1
·
answered by sweetie 5
·
7⤊
1⤋
Assuming that "x" between the 9 and the x^8 is a multiplication sign, and you mean ((27x)/9)*((x^8)/(3x^5))...
We can rearrange the first term as (27/9)*x, which is equal to 3x
3x * ((x^8)/(3x^5))
Because dividing powers with equal bases is equivalent to subtracting the exponents, we can rearrange that second term as
(x^(8-5))/3 = (x^3)/3
and plug that back in, and go from there:
3x * (x^3)/3
(3*x*x^3) / 3
x* x^3
x^4
2006-10-11 07:28:44
·
answer #2
·
answered by hogan.enterprises 5
·
0⤊
0⤋
I'll assume you mean (27x/9) * (x^8 / (3x^5)). You really should use parentheses to make it clearer, though.
27x/9 reduces to 3x.
For x^8 / (3x^5), use a^x/a^y = a^(x-y) and get x^3/3.
Multiply the two: 3x * x^3 /3 = x^4.
2006-10-11 07:24:33
·
answer #3
·
answered by James L 5
·
1⤊
0⤋
x^4.
(27x/9 x x^8/3x^5=27x/9 * x^8/3x^5)
LET US SEPERATE TWO PARTS:
27x/9 , x^8/3x^5
27x/9 =9*3*x/9
=3x
x^8/3x^5
=x^(8-5)/3
=x^3 / 3
27x/9 * x^8/3x^5
=3x*x^3 / 3
=x^(3+1)
=x^4
2006-10-11 08:11:51
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
-6(x-6) = 2x - 36 the 1st step: do away with the brackets = -6x + 36 = 2x -36 Step 2: separate the x values from the numerical values upload 36 to the two edge -6x + 36 +36 = 2x -36 +36 = -6x + 72 = 2x upload 6x to the two edge -6x + 6x +72 =2x + 6x 72 = 8x Step 3 Dived the two sides by using the x fee 72 / 8 = 8x / 8 9 = x the respond is X = 9
2016-11-27 21:57:03
·
answer #5
·
answered by ? 3
·
0⤊
0⤋
if these are 2 separet equations then
27x/9x=3
x^8/3x^5=x^3/3
2006-10-11 07:18:28
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
3x*(x^3/3)=x^4
2006-10-11 07:24:22
·
answer #7
·
answered by raj 7
·
0⤊
0⤋
You need to make it more clear. Use ()
2006-10-11 07:17:19
·
answer #8
·
answered by Mariko 4
·
0⤊
0⤋